The last, the most dreadful resource of nature': Economic-historical reflections on famine - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2016)
The lecture paper focuses on some topics that remain current in famine studies. First, it reviews the link between food prices and the severity of famines as reflected in excess mortality. Second, it places the death tolls from several recent famines in sub-Saharan Africa in historical context. Third, it reviews the impact of famines on fertility. Famines are always associated with a reduction in births; but to what extent are those births lost or births postponed? Fourth, it reviews the literature that invokes famines as a testing ground for the foetal origins hypothesis. Finally, it reviews the prospect of a near future in which famines have been consigned to history.
Keywords: 330; famine; malnutrition